Pengaruh Teknologi terhadap Minat Baca pada Anak-anak di Desa Citasuk : Studi Kasus Rendahnya Kemampuan Literasi Membaca pada Anak-anak di Desa Citasuk - Andini Restu Fitriani; Abel Adhaprilliani; Indriyani Andiska; Elsa Rosania Nabilla; Agam Mukyi; Azzahra Hanifah; Jihan Camila Amru; Rizki Amilia; Mohamad Ikrom Arasid (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Education is a deliberate effort to pass on cultural heritage from one generation to the next. It aims to shape the younger generation to be role models for the previous one. The Community Service method, through a Service Learning (SL) approach, involves applying acquired knowledge to assist the community through direct interaction and providing solutions to their problems. The KKM Group 31 students in Desa Citasuk offer a solution to enhance reading literacy among young children in the area by setting up a Reading Corner. This initiative aims to encourage children to develop a love for reading by providing a variety of books and resources. Reading literacy is crucial for young children in their growth and development. Therefore, community service activities like this KKM project enable students to impart knowledge beyond the classroom while gaining practical experience outside of it. Additionally, the Reading Corner motivates children and boosts their literacy skills.